2014
DOI: 10.1179/2045772314y.0000000259
|View full text |Cite
|
Sign up to set email alerts
|

Satisfaction with upper extremity surgery in individuals with tetraplegia

Abstract: Objective: To supplement the scant information available regarding the satisfaction of patients with tetraplegia following upper extremity reconstructive surgery for such individuals with spinal cord injury (SCI). Study design: Retrospective study with questionnaire follow-up. Setting: The Danish Spinal Cord Injury Centers. Material and methods: In the initial review period, 119 upper extremity surgeries were performed on patients with tetraplegia (n = 49). Seven died and the remaining 42 were invited to compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
7
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 31 publications
(25 reference statements)
3
7
1
Order By: Relevance
“…The activities in which participants' function was improved after surgery were similar to the activities mentioned in the Danish study by Gregersen et al 19 …”
Section: Discussionsupporting
confidence: 79%
“…The activities in which participants' function was improved after surgery were similar to the activities mentioned in the Danish study by Gregersen et al 19 …”
Section: Discussionsupporting
confidence: 79%
“…These results are in accordance with the findings of previous studies linking Upperlimb surgery to ICF domains. 4,14,29 Clearly, patients' perception of satisfaction after upper-limb tetraplegia surgery is very high, [18][19][20][21] and the gains could be linked to the ICF categories body functions/ structures and activity. The more active joints a person has, the better the ability to grasp, release and manipulate an object.…”
Section: Discussionmentioning
confidence: 99%
“…Ninety-five percent responded that the surgery had been beneficial, which is similar, albeit slightly higher as compared with previous studies conducted in the United States, the Netherlands and Denmark, where the proportion of positive responses ranged between 80 and 90%. [19][20][21] In the Swedish satisfaction survey, it was concluded that surgical interventions are rewarding from a patient perspective, because they lead to improvements in daily life as well as enhanced quality of life. 18 None of the previous satisfaction surveys conducted in the United States, the Netherlands and Denmark have used the ICF to interpret the results.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the cervical spinal cord injuries, impaired arm and hand function is straight connected to the loss of functional independence level in quadriplegics 1 and recovery of Upper Limb (UL) movements is essential for the rehabilitation of these individuals. Several therapeutic interventions are used, in an attempt to improve the sensory and motor deficits, such as tendons transfers, orthosis and Neuromuscular Electrical Stimulation (NMES) 1,2 .…”
Section: Introductionmentioning
confidence: 99%